Problematika Kompetensi Pedagogik Guru PAI di Pondok Pesantren Bahrul Ulum Tambakberas Jombang - Muhammad Ichlasul Amal; Anis Humaidi (Lembaga Yasin AlSys, 2026)
Pedagogical competence is a fundamental competency that every Islamic Religious Education (PAI) teacher must possess, particularly in the context of pesantren, which demands the integration of mastery of religious subject matter with professional learning management skills. However, the reality at Pondok Pesantren Bahrul Ulum Tambakberas Jombang shows that the pedagogical competence of PAI teachers is not yet optimal, especially in relation to lesson planning, the implementation of active learning, the use of instructional media and technology, and the conduct of authentic assessment. This study aimed to analyze in depth the forms of pedagogical competence problems among PAI teachers and the factors influencing their emergence. The research employed a qualitative approach with a case study design, with data collected through in-depth interviews, participatory observation, and documentation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing, while data trustworthiness was ensured through source and technique triangulation. The findings indicate that the problems in PAI teachers’ pedagogical competence include: (1) the preparation of learning tools that is not yet systematic; (2) the use of conventional teaching methods with minimal variation; (3) suboptimal utilization of instructional technology; and (4) learning evaluation that tends to be cognitively oriented. The main contributing factors include high teaching loads, limited access to professional training, a pesantren culture that is more oriented toward traditional kitab learning, and limited supporting facilities. These findings underscore the need for strategic interventions through the enhancement of teachers’ professional competence, structured pedagogical training, and the strengthening of quality management of instruction based on both pesantren and national curricula. In conclusion, strengthening the pedagogical competence of PAI teachers at Pondok Pesantren Bahrul Ulum Tambakberas Jombang requires institutional support and sustainable capacity-building programs, including the renewal of pedagogical practices so that they are aligned with contemporary learning needs.